2016
DOI: 10.1515/cclm-2015-0358
|View full text |Cite
|
Sign up to set email alerts
|

Liquid citrate acidification introduces significant glucose bias and leads to misclassification of patients with diabetes

Abstract: Inhibition of glycolysis is most effectively achieved using liquid citrate acidification, compared to LiH, NaF/KOx or serum. Due to clinically significant bias relative to reference glucose, the interchangeable use of different tube types for serial glucose measurements is not recommended. The replacement of NaF/KOx with Glucomedics tubes substantially impacts glucose results, giving marked rise in diabetes prevalence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 27 publications
1
2
0
Order By: Relevance
“…Citrate is an important intermediate product in the TCA cycle and is also the terminal metabolic pathway and metabolic linkage of lipid biosynthesis. Previous studies found that citrate was significantly increased in the DM rats and liquid citrate acidification can most effectively inhibit glycolysis [38,39], which are consistent with our finding that the level of citric acid increased in the model group and decreased in the HD group. Citric acid can reversibly produce isocitrate under the action of aconitase, and the isocitrate dehydrogenase (ICD) is a key rate-limiting enzyme in the TCA cycle.…”
Section: Energy Metabolismsupporting
confidence: 92%
“…Citrate is an important intermediate product in the TCA cycle and is also the terminal metabolic pathway and metabolic linkage of lipid biosynthesis. Previous studies found that citrate was significantly increased in the DM rats and liquid citrate acidification can most effectively inhibit glycolysis [38,39], which are consistent with our finding that the level of citric acid increased in the model group and decreased in the HD group. Citric acid can reversibly produce isocitrate under the action of aconitase, and the isocitrate dehydrogenase (ICD) is a key rate-limiting enzyme in the TCA cycle.…”
Section: Energy Metabolismsupporting
confidence: 92%
“…The first lyophilized citric-citrate buffer additive was replaced by a liquid additive that required the use of a controversial dilution factor ( 17 - 19 ). But, since 2017, it has been replaced by a validated lyophilized additive ( 16 , 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…The highest drop of glucose concentration was observed in the serum tube, then in NaF/KOx followed by lithium-heparin tube sampled on ice. Liquid citrate tube preserved glucose concentration the best ( 25 ). These results underline the risks associated with usage of serum tube for glucose concentration measurement: misdiagnosis of diabetes patients and falsely decreased glucose concentration.…”
Section: Discussionmentioning
confidence: 99%